Bread - Loomis, Alice M. (My University, 1904)
Introduction: It is said that the civilization of a people may be judged by the bread they make. The more one reads of bread in history the more he is inclined to believe this statement. From the earliest recorded times, all but the most savage people have used bread in some form. We find, in the oldest records of Egypt, that each woman then ground her own grain between two stones, mixed the flour with water and then baked it on hot stones or in the ashes. But by the time the Isrealites came to Egypt, leavened bread was in common use. The yeast plant, that we know now, was grown by the ancient Greeks. Microscopic examination of bread found in buried Pompeii shows the form of yeast that we use to-day. The pure strong yeast to be found in all markets and the carefully milled flour of the present time make possible a bread unobtainable among barbarians or any less civilized people. In spite of all this, poor bread is lamentably common. Good light bread is a palatable, digestible and nutritious food, and from an economical as well as dietetical standpoint holds an important, one may almost say first, place among our foods.
Bread making
Citation: Loomis, Alice M. Bread. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Bread; Food; Nutrition; Food Processing; Food Composition; Theses